Palladio a colori, Palladio in bianco e nero: il mito del bianco nell’architettura palladiana - Paternò, Damiana Lucia (Opus Incertum, 2017)
In Palladio's architecture the choice of colour is strictly related to the use of specific materials: stone, plaster, rectified bricks. His buildings can vary from the candid white of Istrian stone, to the warmer tones of Vicenza stone, and the bright red that characterises some of his buildings at the beginning of his Venetian period. The Four Books of Architecture, although at the origin of Palladio's fame, have created the dogma of an exclusively monochrome Palladio, white and stony. From the early 17th century, the parts in red stucco were often hidden under layers of 'fake stone' plaster with the purpose of correcting what was considered to be an error ascribable to unqualified craftsmanship and problems related to the construction site. An interpretation which was considered accurate until very recently, then refuted in the last decades of the 20th century thanks to a more careful attention to the materiality of Palladio's built structures.